Hubungan Pola Menyusui dengan Fekuensi Kejadian Sakit pada Bayi - Putri, Rismaina; Illahi, Suci Aji (Journal of Issues in Midwifery, 2017)
ABSTRACTBased on data coverage of exclusive breastfeedingin Malang on 2014,the coverage of exclusive breastfeeding was 74.13%, while complete exclusive breastfeeding was 56.98%. This achievement had exceeded the target of 72%. Meanwhile, according to data from the Health Service of Malang, on 2014, therewas 871 pneumonia cases, 5405 cough not pneumonia cases, and 1540 diarrhea cases in infants. Those three diseases were the most common cases that occurred to 0-12 months-old infants in Malang. This study aimed to investigate the correlation between breastfeeding patterns with frequency of illness in infants. This study was an observational study with cross sectional design.Sampling method in this studyused purposive sampling method. Result of this study showed that based on statistical test result, the value of likelihood ratio is 0,00 (p<0,05). It means that the pattern of breastfeeding had a relation with the frequency of illness in infants.The conclusion from this study is there is significant relationship between the pattern ofbreastfeeding with the frequency of infantsillness in Pandanwangi,Blimbing district, Malang City.